A review on the role of amino acids in gas hydrate inhibition, CO 2 capture and sequestration, and natural gas storage - Bavoh, C.B. (2019)
Natural amino acids have been introduced as potential additives for gas hydrate inhibition, natural gas storage, and CO 2 capture and sequestration. Herein, almost all amino acids hydrate-based additives are critically reviewed. The hydrate inhibition/promotion effect of each amino acid and factors that affect their performance on gas hydrate formation are discussed. Furthermore, amino acids hydrate inhibition/promotional mechanism and modelling studies are reviewed. Detailed comparison between amino acids and convention hydrate additives alongside future directions towards amino acids hydrate-based technology commercialization are also discussed. The findings presented in this work are relevant for future amino acids breakthrough research in hydrate-based technologies. Â© 2019 Elsevier B.V.